2020
DOI: 10.1049/sfw2.12014
|View full text |Cite
|
Sign up to set email alerts
|

Requirements engineering for crossover services: Issues, challenges and research directions

Abstract: Crossover services involve deep convergence of services in different domains. Requirements analysis of crossover services often requires the collaboration of engineers in different domains and various organizations. The industry has a demand for sophisticated requirements engineering (RE) methods to address challenges brought by crossover and convergence. However, many methods proposed by researchers have not been widely used in the industry, and the reason is that these methods provide technological solutions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…3) More adaptive syntactic processing Many studies have concluded that there is a gap between RE tasks automation research and its implementation undertaken in industrial and real-life projects [147]- [149]. This gap is more obvious in the case of rule-based approaches since they usually need the requirements to be represented based on specific templates [150]; hence, their success strongly depends on the consistency of the requirements with the predefined templates [114], [150].…”
Section: ) More Re Domain-specific Word Embedding Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…3) More adaptive syntactic processing Many studies have concluded that there is a gap between RE tasks automation research and its implementation undertaken in industrial and real-life projects [147]- [149]. This gap is more obvious in the case of rule-based approaches since they usually need the requirements to be represented based on specific templates [150]; hence, their success strongly depends on the consistency of the requirements with the predefined templates [114], [150].…”
Section: ) More Re Domain-specific Word Embedding Modelsmentioning
confidence: 99%
“…These situations are common in real-life projects when it is hard to control requirements authoring environments, especially in large development projects, or when one has little control over the requirements authoring environments. [12], [114], [147]- [151]. One of the potential future research directions is working on more adaptive approaches which can be more flexible when handling requirements, such as identifying the syntactic structures automatically and building more adaptive approaches based on the dynamically identified structure.…”
Section: ) More Re Domain-specific Word Embedding Modelsmentioning
confidence: 99%
“…Many studies have concluded that there is a gap between RE tasks automation research and its implementation undertaken in industrial and real-life projects [147,148,149]. This gap is more obvious in the case of rule-based approaches since they usually need the requirements to be represented based on specific templates [150]; hence, their success strongly depends on the consistency of the requirements with the predefined templates [114,150].…”
Section: More Adaptive Syntactic Processingmentioning
confidence: 99%
“…These situations are common in real-life projects when it is hard to control requirements authoring environments, especially in large development projects, or when one has little control over the requirements authoring environments. [114,151,147,148,149,150,12]. One of the potential future research directions is working on more adaptive approaches which can be more flexible when handling requirements, such as identifying the syntactic structures automatically and building more adaptive approaches based on the dynamically identified structure.…”
Section: More Adaptive Syntactic Processingmentioning
confidence: 99%
“…The importance of Requirements Engineering (RE) in software development has been mentioned in many works of literature including in Gregory, [8], Hidellaarachchi et al, [10], Liu et al, [13] Wiecher et al, [26]. In general, the generic RE activities are requirements elicitation, analysis and modelling, negotiation, validation, documentation, and management.…”
Section: Introductionmentioning
confidence: 99%